Pengolahan Lindi Menggunakan Advanced Oxidation Process (AOPs) Berbasis Ozon - Rahmayanti, Ardhana; Reta Slakhul Faradila; Ani Masrufah; Puput Anggraini Permata Sari (Journal of Research and Technology, 2022)
Leachate can be formed from the percolation of water that passes through the garbage. The high content of organik and metallic substances in leachate can cause environmental damage, so it must be treated first before being discharged into the environment. This study aims to determine the effectiveness of ozonation in neutralizing pH and reducing the levels of TSS, BOD, COD in the leachate of the Griyo Mulyo landfill using the AOPs method based on ozonation. Studies on ozonation in leachate treatment have been carried out by varying the ozonation time (15, 30, 45, and 60 minutes). Parameters that have been observed are pH, TSS, BOD, COD. The results showed that the best ozonation time for leachate pH was at 15 minutes with a value of 7, the best ozonation time for leachate TSS was at 15 minutes with a value of 56 mg/L. The best ozonation time for BOD and COD was at 45 minutes with values ​​of 511 mg/L and 1260 mg/L, respectively.  The best percentage of removal efficiency for TSS, BOD and COD reached 67%; 84.1%; and 88.41%.